2018
DOI: 10.1021/acs.orglett.7b03760
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I)-Catalyzed Intramolecular SEAr Reaction: Efficient Synthesis of Isoxazole-Containing Fused Heterocycles

Abstract: Intramolecular electrophilic aromatic substitution (SAr) reaction at the 5-position of isoxazoles was achieved. The electron-donating heteroatoms (N and O) at the 4-position of isoxazoles, which can be readily prepared based on our originally developed synthetic procedure, and a cationic gold(I) catalyst are essential for the intramolecular SAr reaction to synthesize isoxazole-containing fused heterocycles. Structurally diverse isoxazolopyridines 6 and isoxazolopyrans 9, including base-labile 3-unsubstituted d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…However, there is no report of N–O bond cleavage of 3-unsubstituted isoxazolopyridines. Therefore, the N–O bond cleavage of previously synthesized isoxazolopyridine 9a (19) was first examined under various acidic and basic conditions (Table 1). Among Bro̷nsted acid mediated conditions (entries 1–4), aqueous HCl in MeOH conditions (entry 1) afforded 5a in 70% yield with complete conversion of 9a .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is no report of N–O bond cleavage of 3-unsubstituted isoxazolopyridines. Therefore, the N–O bond cleavage of previously synthesized isoxazolopyridine 9a (19) was first examined under various acidic and basic conditions (Table 1). Among Bro̷nsted acid mediated conditions (entries 1–4), aqueous HCl in MeOH conditions (entry 1) afforded 5a in 70% yield with complete conversion of 9a .…”
Section: Resultsmentioning
confidence: 99%
“…Column chromatography was performed on Silica Gel 60 N, purchased from Fuji Silysia Chemical Ltd. 4-Propargylaminoisoxazoles 8 and isoxazolopyridines 9 and 10 were prepared in accordance with the previously reported procedure. 19 Spectral data for 8i and 9i (newly prepared compounds) are shown below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the authors demonstrated that the addition of an external hydride acceptor as N -phenylbenzaldimine increased the yield in the synthesis of isoxazolopyridines ( 146 , X = NH). Remarkably, the use of bulky gold(I)-complexes, such as [JhonPhosAu] + , is essential for the satisfactory formation of products (Morita et al, 2018).…”
Section: Gold-catalyzed Isomerization Processes Involving An Initimentioning
confidence: 99%
“…10 Lately, Morita and co-workers reported intramolecular electrophilic aromatic substitution reaction only occurred at the 5-position of isoxazole rather than at the 3-position. 11 Herein, we investigated the effect of the groups at C3 and C5 positions of the isoxazole on the Sonogashira cross-coupling reaction.…”
Section: Introductionmentioning
confidence: 99%